اعتبار الشريعة الإسلامية لمعيار القوت في أحكام المعاملات المالية - تجيني ،عز الدين (University of Eloued جامعة الوادي, 2024)
"جاء هذا البحث لبيان معنى القوت والغذاء، وبيان أهمية تحقيق الأمن الغذائي في الإسلام، ودور الغذاء في حفظ النفس البشرية والصحة الإنسانية وحفظ أمن واستقرار الدول سياسيا واجتماعيا. كما يبين هذا البحث دور الشريعة الإسلامية في تحقيق الامن الغذائي بمختلف علومها الفقهية والاصولية والمقاصدية، انطلاقا من انتاج الغذاء من خلال الحث على زراعة الأرض وسقيها واستصلاحها. الى توزيعه، من خلال الزكاة والاوقاف والنفقة ...، الى تخزينه اقتصادا حفظا دون احكتار او ربا او تبذير. هذا وقد بينت افضلية القوت كالحبوب والتمر على غيره من الطعام، كما أشرت فيه الى سلاح الغذاء الذي تستعمله الدول الكبرى لتضييق على الدول الإسلامية واخضاعها خاصة في زراعة الاقوات واحتكار زراعة الحبوب. كما اشرت فيه الى قصة يوسف عليه السلام نموذجا في تحقيق الامن الغذائي، وخطته المحكمة في مواجهة المجاعة التي ضربت مصر لسبع سنين. ثم بينت فيه بعض الاحكام الشرعية لما توفره الدولة الجزائرية من قروض لدعم الفلاح من خلال ""بنك بدر"" وما فيها من مخالفات شرعية، خاصة وان بعض هذه القروض موجه لزراعة الحبوب في سبيل تحقيق الامن الغذائي والاكتفاء الذاتي المنشود."This research came to explain the meaning of cereals and food, and explain the importance of a chieving food security in islam and the role of food in preserving the human soul and human health and preserving the security and stability of countries politically and socially. This research also shows the role of Islamic law in achieving food security with its various jurisprudential, fundamental, and purposeful sciences, starting from food production by urging the cultivation, irrigation, and reclamation of land. To distribute it, through zakat, endowments, and maintenance... To store it economically, without monopoly, usury, or waste. In addition, I have demonstrated the superiority of staple foods, such as grains and dates, over other foods. I have also pointed out the food weapon that major powers use to restrict Islamic countries and subjugate them, especially in the cultivation of staple foods and the monopoly of grain cultivation. I also referred to the story of Joseph, peace be upon him, as a model for achieving food security, and his precise plan to confront the famine that struck Egypt for seven years. Then I explained in it some of the legal provisions of the loans provided by the Algerian state to support farmers through “Badr Bank” and the legal violations that therein, especially since some of these loans are directed to growing grains in order to achieve the desired food security and self-sufficiency.
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: الشريعة الاسلامية; أحكام المعاملات المالية; معيار القوت; Islamic Sharia; Financial Transactions Provisions; Food Standard.